Gambaran Pencegahan Stunting Di Indonesia: Studi Literatur - Jelita Siska Herlina Hinonaung; Erick Johans Manoppo (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: The purpose of the study was to determine the description of stunting prevention in Indonesia based on a literature review.Methods: The research method used is a literature study. Data collection by searching for Indonesian-language articles on the Google Scholar database with a time span of 2020-2022. The keywords used are